Iris recognition through transfer learning and exponential scaling - et. al., Mr. Keyur Shah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper, we investigate deep learning framework for iris recognition by embedding exponential scaling using transfer learning. By employing exponential scaling transformation technique, we examine the effect of in fine-tuned pre-trained MobileNetV2 model. The performance of the model is evaluated for various scaling techniques by conducting an experiment on well-known two public iris dataset. The results of the experiment show the exponential scaling operation outperforms in comparison with the linear scaling.